Promises and Pitfalls: Using an AI Chatbot as a Tool in 5E Lesson Planning - Goodman, Jeff; Handa, Vicente; Wilson, Rachel E.; Bradbury, Leslie U. (Innovations in Science Teacher Education, 2024)
The authors describe how we approached using an AI chatbot, ChatGPT, during the spring 2023 semester with preservice elementary education students as an exercise in thinking about planning 5E lessons. We report here how we explored the tool with four different sections of preservice teachers and what we found about using this particular AI chatbot to help them develop planning skills for inquiry-based science instruction. Specifically, we found that when using a single prompt, the tool was not reliably accurate or realistic in planning for real classrooms or creating quality 5E lessons. However, when we employed techniques to focus and refine our prompts, we found value in using the chatbot as a part of brainstorming, and we determined that ChatGPT was particularly useful for generating high-quality, open-ended questions. Our overall conclusion from the experience is the importance of scaffolding students to use AI chatbots in an iterative process, focusing on creating high-quality prompts and successive questioning to get useful output information. Opportunities and cautions for using such tools in education are reviewed.